Frontiers: Machines vs. Humans: The Impact of Artificial Intelligence Chatbot Disclosure on Customer Purchases - Luo, Xueming; Tong, Siliang; Fang, Zheng; Qu, Zhe (Marketing Science, 2019)
Chatbot identity disclosure negatively affects customer purchases because customers perceive the disclosed bot as less knowledgeable and less empathetic.